University Electronic Records Management System for Northwest Samar State University, Calbayog City - Donald M. Patimo; Ritchie P. Maribojoc (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Effective records management program is a major element of the governance of any organization. Based from the surveys, the Northwest Samar State University was not fully aware on how to do about the implementation of this act, National Archives of the Philippines Act of 2007 (R.A 9470). The university was still relying from the university code for the records management provisions. This study was undertaken to develop and validate the acceptability of the developed University Electronic Records Management System (UeRMS) for Northwest Samar State University as perceived by the computer experts, school officials, teaching personnel and non- teaching personnel. Thus, the idea and assessment of the respondents towards the design of the system is very critical. Upon validating the developed system, they observed that it was much faster to search records compared to manual process.